(untitled) (The Science Post, 2026)
The bilingual education system, where Arabic and English are used throughout the primary, secondary, and higher education in Kuwait, is the key to achieving both global competence and cultural and linguistic identity. Although this system has strengths, it has issues to do with the lack of individualized language use, limited classroom time, and lack of feedback opportunities, especially when it comes to second language acquisition. The recent developments in the sphere of artificial intelligence (AI), namely chatbots driven by AI, offer some perspective of overcoming these drawbacks, through adaptive, interactive, and learner-driven language assistance. This paper evaluates the use of AI chatbots in improving the acquisition of both Arabic and English languages in Kuwait, which has a bilingual education system. Based on the available literature and the contextual analysis, the study examines the way AI chatbots can facilitate personal practice, learner autonomy, and the development of listening, speaking, reading, and writing skills in a balanced manner. Also, the paper considers the pedagogical advantages, practical issues, and general implications of inclusion of chatbot technologies, paying specific focus to technological preparedness, the views of educators, and the student involvement and achievement. The results are expected to be useful in the context of making informed choices about the successful implementation of AI chatbots in the bilingual education system and in the context of the creation of supportive, inclusive, and culturally sensitive language learning experiences in Kuwait.